Growth rates, biomass yield and forage quality of three local Poaceae in Annaba’s region, North East Algeria - Boudelaa M.; Slimani S.; Ladjama A.; Benkadour M.; Nadjeh I. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
In the Algerian context, the development of durable fodder agriculture and breeding require complex strategies of which one of the elements consists in developing the use of fodder species adapted to the local biotope characteristic of Mediterranean climate. The aim of this work consisted to study and cultivates 3 Algerian varieties of Poaceae fodder, reed canary grass Phalaris arundinacea, rye grass Lolium multiflorum and tall fescue Festuca arundinacea in order to evaluate their agronomic performance; the growth rates and the field biomass output. The obtained results showed that the biomass production was more important for the reed canary grass in compete cycle than in incomplete cycle of vegetation, contrary to rye grass and tall fescue. Moreover, the analysis of growth kinetics showed that it is the spring growth which presented the best characteristics of the plant development and dry matter (DM) yield production. From fodder value, the reed canary grass and the tall fescue are well provided in Total Nitrogen Matter (TNM) and relatively low in Fodder Units (FU). Contrary, the rye grass is rich in energy compounds (EU) but contains low protein content.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)